PERAN MAHASISWA MAGANG DALAM TRANSFORMASI PERENCANAAN PEMBANGUNAN DAERAH BERBASIS RISET DAN INOVASI DI BAPPEDA KABUPATEN DAIRI - Rita Hati Ndruru; T. Sihol Nababan2 (DEVELOPMENT: Journal of Community Engagement, 2026)
Indonesian development planning still relies on traditional methods involving annual routines, resulting in limited access to data, research findings, and innovation. The complexity of development issues, such as climate change, technological advancements, and community needs, requires more evidence-based design. In this regard, the Dairi Regency Development Planning Agency (Bappeda) plays a crucial role in driving changes in regional development planning toward a more research- and innovation-based approach. This study aims to examine the process of this change in development planning practices in Dairi Regency. The method used in this study is a descriptive qualitative approach, with data collection techniques including direct observation of the planning process, analysis of regional planning documents and policies, and searching for available development data online. The findings indicate that the Dairi Regency Development Planning Agency (Bappeda) has begun to integrate development data such as the Human Development Index, poverty levels, and Gross Regional Domestic Product (GDP) as a basis for formulating programs and activities. Furthermore, the use of planning information systems and the application of innovation in policymaking have also strengthened Bappeda's role as a development planning director. These changes encourage planning that is more measurable, rational, and responsive to regional needs. Therefore, research- and innovation-based planning is a crucial step in strengthening evidence-based regional development policies in Dairi Regency.